Feasibility of Studying Body Composition in Order to Assess and Monitor the Nutritional Status in Children with Congenital Dystrophic Epidermolysis Bullosa - Svetlana G. Makarova; Leyla S. Namazova-Baranova; Nikolay N. Murashkin; Ruslan V. Epishev; Tamara R. Chumbadze; Dmitry S. Yasakov (Педиатрическая фармакология)
Background. Congenital epidermolysis bullosa (CEB) belongs to the group of rare hereditary diseases with severe skin lesions. Congenital dystrophic epidermolysis bullosa (CDEB) is characterized by multiple organ dysfunction accompanied by impaired nutritional status. For a more accurate assessment of nutritional status, planning and control of the efficacy of nutritional support, it is important to assess body composition parameters in addition to anthropometric indices. Our aim was to study the possibility and advisability of using methods for assessing the body composition of children with CDEB. Methods. The study included 43 children with CDEB aged from 2 months to 15 years. Z-scores anthropometric indices weight-for-age (WAZ), height-for-age (HAZ), and bodymass-index-for-age (BAZ) were estimated using the WHO AnthroPlus software. Air displacement plethysmography was performed on the PEA POD (LMi, USA) intended for use in infants. Bioimpedansometry was performed in children older than 6 years according to the standard tetrapolar technique. Results. For children with CDEB, a decrease in the indices of WAZ (-2.24 ± 1.46) and BAZ (-2.5 ± 1.74) is typical. BAZ below -3 (severe nutritional deficiency) is recorded for 21 children. Bioimpedansometry had significant constraints (skin lesion and/or scarring at the sites for standard positioning of electrodes), was performed for 5 study participants and produced erroneous results (the percentage of fat and active cell mass turned out to be normal even in children with moderate and severe nutritional deficiency). Air displacement plethysmography showed correct results, but this method had baby weight and skin state limitations. Conclusion. Methods for assessing the body composition should be applied in clinical practice to assess the nutritional status and its dynamic control in children with CDEB.